Anti-inflammatory effect of Angiotensin 1-7 in white adipose tissue - Nozomi Nishida; Satoru Sugimoto; Satoshi Miyagaki; Chiharu Cho; Madoka Konishi; Takeshi Goda; Mihoko Yamaguchi; Yasuhiro Kawabe; Hidechika Morimoto; Joji Kusuyama; Takuro Okamura; Masahide Hamaguchi; et al. (Adipocyte)
Obesity is a global health concern that promotes chronic low-grade inflammation, leading to insulin resistance, a key factor in many metabolic diseases. Angiotensin 1–7 (Ang 1–7), a component of the renin-angiotensin system (RAS), exhibits anti-inflammatory effects in obesity and related disorders, though its mechanisms remain unclear. In this study, we examined the effect of Ang 1–7 on inflammation of white adipose tissue (WAT) in dietary-induced obese mice. Monocyte chemoattractant protein-1 (MCP-1) produced by white adipocytes and tumour necrosis factor-α (TNF-α) produced by macrophages are pro-inflammatory cytokines and interact to form a pathogenic loop to exacerbate obesity-induced inflammation. We found that Ang 1–7 reduced MCP-1 and TNF-α gene expressions and the number of crown-like structures, which are histological hallmarks of the pro-inflammatory process, in visceral epididymal WAT (eWAT) and reduced circulating MCP-1 and TNF-α levels, accompanied by improvement in insulin resistance, in dietary-induced obese mice. Furthermore, Ang 1–7 reduced MCP-1 and TNF-α secretions in 3T3-L1 white adipocytes and RAW 264.7 macrophages, respectively, which are in vitro experimental models mimicking obesity condition. Our results suggest that Ang 1–7 directly acts on WAT to mitigate obesity-induced inflammation. Thus, this study provides novel insights into the underlying mechanism of anti-obesity effects of Ang 1–7.